An investigation of the potential of rhodamine B hydrazide as a fluorescent probe for enhancing latent fingerprints - Nadeem Muhammad; Amjad Ali; Hairong Cui; Abdullatif Bin Muhsinah; Muhammad Abdul Qadir; Ghulam Mustafa Kamal; Jalal Uddin; Shoaib Munir (Results in Chemistry)
A series of novel rhodamine B hydrazide derivatives were synthesized by refluxing rhodamine B hydrazide with various aromatic aldehydes, including 3-nitrobenzaldehyde, 4-nitrobenzaldehyde, 4-chlorobenzaldehyde, 4-hydroxybenzaldehyde, cinnamaldehyde, piperonal, and veratraldehyde. The resulting hydrazones were purified and characterized through techniques including melting point determination, UV–Vis spectroscopy (λmax ranging from 245 to 555 nm), infrared (IR) spectroscopy, and proton nuclear magnetic resonance (NMR) spectroscopy. The derivatives exhibited strong fluorescence with enhancements up to 90 % at optimized wavelengths, facilitating their use in latent fingerprint visualization. Yields of the purified derivatives exceeded 85 %, with melting points in the range of 172–188 °C. Notably, certain derivatives enhanced latent fingerprint contrast by up to 60 % on glass surfaces, indicating significant potential in forensic applications. This study demonstrates a cost-effective and environmentally friendly synthesis method that provides high yields of pure fluorescent agents suitable for forensic science.